"Measuring" music therapy: problems, challenges, outlooks between theory and clinical practice. Issue 1 (1st June 2016) - Toshimori, Kumiko; Colletti, Angelo; Rijoff, Riccardo; Rodocanachi, Marina
Abstract : Background : One of music therapy's crucial points is its scientific validation. Nevertheless, the Italian National Health Service asks for a measurement of treatment's effectiveness to decide about the allocation of resources. Objective : The authors' aim is to present an instrument to collect and analyse data during music therapy sessions, outline the profiles of activation and countenance and the level of personal harmonization. Discussion : Music therapy promotes, inside a therapeutic relationship, processes of integration, harmonization and psychophysical well-being. Therefore, we rejected a mere quantitative performance evaluation, choosing a statistical measurement which points out the item's variability, to assess the patient's harmonization, meant as balance and elasticity of the person's functions in the interaction with the environment. Methods : Moving from clinical experience, the authors created a table divided into the areas of active and receptive music therapy, a tool which permits to evaluate, through numeric score, the harmonization and integration of the patient in terms of activation and countenance. Conclusions : Purpose of this intervention is to show the utility, the critical issues and the potential of this instrument in a rehabilitation context, and to think about relational therapy measurableness.